PENGARUH CORPORATE GOVERNANCE DAN OVERVALUED EQUITY TERHADAP STOCK PRICE CRASH RISK - Widaad Ariiq Farizaki (2022)
This study is a quantitative study that aims to determine the effect of corporate governance and overvalued equity on stock price crash risk in primary consumer goods (consumer non-cyclicals) companies listed on the Indonesia Stock Exchange for the 2016-2019 period. The purposive sampling method was used by researchers to determine the research sample and consisted of 98 observations from 32 companies that matched the sample selection criteria. Multiple linear regression analysis with the help of SPSS 26 application was used to test the hypothesis. The results of the study state that board of commissioners have a significant effect on stock price crash risk, managerial ownership has no significant effect on stock price crash risk, institutional ownership has no significant effect on stock price crash risk, and overvalued equity has a significant effect on stock price crash risk.